2012
DOI: 10.2478/v10011-012-0013-2
|View full text |Cite
|
Sign up to set email alerts
|

Quality Indicators of the Pre-Analytical Phase

Abstract: Summary: Quality indicators are tools that allow the quantification of quality in each of the segments of health care in comparison with selected criteria. They can be defined as an objective measure used to assess the critical health care segments such as, for instance, patient safety, effectiveness, impartiality, timeliness, efficiency, etc. In laboratory medicine it is possible to develop quality indicators or the measure of feasibility for any stage of the total testing process. The total process or cycle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Five patients were on ERT, while six patients were treatment naïve at the time of the study. The patients' characteristics (age at diagnosis, sex, chitotriosidase level, severity score index (SSI) (3)(4)(5), prior to ERT institution, type of mutation and ERT) are presented in Table I.…”
Section: Resultsmentioning
confidence: 99%
“…Five patients were on ERT, while six patients were treatment naïve at the time of the study. The patients' characteristics (age at diagnosis, sex, chitotriosidase level, severity score index (SSI) (3)(4)(5), prior to ERT institution, type of mutation and ERT) are presented in Table I.…”
Section: Resultsmentioning
confidence: 99%
“…Since many risk factors, such as obesity, hypertension, dyslipidemia, diabetes and smoking are common for both arterial and venous thromboses, it has been suggested that VTE should be considered as a part of a pancardiovascular syndrome, along with coronary artery disease, peripheral artery disease and cerebrovascular disease (72).…”
Section: Cardiovascular Riskmentioning
confidence: 99%
“…In order to avoid misinterpretation of the test results, laboratory experts should report the potential causes of false-positive and falsenegative test results using interpretative comments along with the test result reports (140,141).…”
Section: When Should Investigation Be Performed?mentioning
confidence: 99%